Supernovae and transients with circumstellar interaction. Issue 7 (8th July 2020) - Fraser, Morgan
Abstract : It is 30 years since the characteristic signatures of interaction with circumstellar material (CSM) were first observed in a core-collapse supernova. Since then, CSM interaction has been observed and inferred across a range of transients, from the low-energy explosions of low-mass stars as likely electron-capture supernovae, through to the brightest superluminous supernovae. In this review, I present a brief overview of some of the interacting supernovae and transients that have been observed to date, and attempt to classify and group them together in a phenomenological framework.